2015
DOI: 10.1104/pp.15.01405
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of plant primary metabolism in response to insect herbivory

Abstract: ORCID IDs: 0000-0002-3643-7875 (S.Z.); 0000-0002-4716-4323 (Y.-R.L.); 0000-0002-5912-779X (V.T.); 0000-0002-9675-934X (G.J.).Plants in nature, which are continuously challenged by diverse insect herbivores, produce constitutive and inducible defenses to reduce insect damage and preserve their own fitness. In addition to inducing pathways that are directly responsible for the production of toxic and deterrent compounds, insect herbivory causes numerous changes in plant primary metabolism. Whereas the functions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
247
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(270 citation statements)
references
References 101 publications
11
247
1
2
Order By: Relevance
“…The biosynthesis of tryptophan, glutamine and glutamic acid are induced in herbivore‐infested plants. The overproduction of these amino acids seems to serve as precursors for inducible defence metabolites (Brotman et al ., 2012; Rojas et al ., 2014; Zhou et al ., 2015). In our study, the leaves of T. gamsii F18‐treated plants had more tyrosine, tryptophan, serine, oxoproline, ornithine, phenylalanine, lysine, glutamine, glutamic acid, cyanoalanine, citrulline, aspartic acid and asparagine compared to the control plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biosynthesis of tryptophan, glutamine and glutamic acid are induced in herbivore‐infested plants. The overproduction of these amino acids seems to serve as precursors for inducible defence metabolites (Brotman et al ., 2012; Rojas et al ., 2014; Zhou et al ., 2015). In our study, the leaves of T. gamsii F18‐treated plants had more tyrosine, tryptophan, serine, oxoproline, ornithine, phenylalanine, lysine, glutamine, glutamic acid, cyanoalanine, citrulline, aspartic acid and asparagine compared to the control plants.…”
Section: Discussionmentioning
confidence: 99%
“…For example, tryptophan plays a critical role in regulating plant responses to biotic and abiotic stresses (Radwanski and Last, 1995; Zhao and Last, 1996; Sangha et al ., 2011). Transcript profiling data generally show herbivory‐induced changes in the expression of genes related to the production of glutamine, glutamic acid, asparagine and aspartic acid (Thompson and Goggin, 2006; Caldana et al ., 2011; Appel and Cocroft, 2014; Zhou et al ., 2015), which are involved in nitrogen assimilation (Coruzzi and Last, 2000). Amino acids also play a role in signal transduction to induce defence gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…While the production of specialized metabolites as defensive molecules is well documented and at times considerable, with, for example, nicotine conditionally containing 6% of the nitrogen in Nicotiana attenuata (Baldwin et al, 1998) and benzoxazinoids constituting up to 2% of the dry matter of some Poaceae (Zuniga et al, 1983), the effects on constitutively abundant metabolites are less frequently considered. In their review, Zhou et al (2015) collate studies looking precisely at these metabolites and comparing specialist versus generalist herbivores (Steinbrenner et al, 2011). The metabolic data, when considered together with collated gene expression data, lead to the intriguing conclusion that, for specialist herbivores, tomato (Solanum lycopersicum) plants change resource allocation rather than produce chemical defense compounds, albeit in a manner that needs to be studied on an interaction-by-interaction basis.…”
mentioning
confidence: 99%
“…They conclude with a perspective of current and anticipated developments of what are already becoming indispensable tools of the plant metabolism. The Updates by Soltis and Kliebenstein (2015) and Zhou et al (2015) cover the use of natural variance for the identification of key genes regulating the accumulation or degradation of metabolites and the lesser discussed effects of plantinsect interactions on primary metabolism of the plant, respectively. The first of these provides both mechanistic and evolutionary insights as well as discusses the predominance of the influence of organellar genomes (Joseph et al, 2013) and the sheer breadth of loci that combine to underlie the complex genetic architecture of the metabolome.…”
mentioning
confidence: 99%
“…Indeed, they hypothesise that in the mite saliva there is a wide range of proteins that can act as effectors or elicitors, and its presence will determine the tomato defense outcome. In fact, the proteins present in the saliva of T. urticae vary depending on the host .To circumvent the deleterious effects of plant secondary metabolites and anti- Herbivore attack can also induce changes in plant primary metabolism, such as the reallocation of carbon and nitrogen resources (Steinbrenner et al, 2011;Zhou et al, 2015). The function of these changes for the plant is still not clear, but it has been suggested that they might be used by the plant as a source of energy, as precursors of defense compounds and to hamper herbivore performance by reducing the nutritive value of plant tissue (Zhou et al, 2015).…”
mentioning
confidence: 99%